1972
DOI: 10.1002/bip.1972.360111017
|View full text |Cite
|
Sign up to set email alerts
|

Hydration mobility in peptide structures

Abstract: SynopsisThe structural behavior of hydrochlorides of poly-Llysine and tetraglycine depends on water vapor pressure. At low relative humidities, structural rearrangements are slow. Water molecules catalyze these structural rearrangements; thus, in tetraglycine hydrochloride, structural transitions are observed at a very low water content of about 1 H,O molecule per 10 peptide residues. Some general aspects of the mechanism of the hydration mobility in peptide structures are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…(1) The time-average conformation of lysozyme in the partially hydrated powder is closely similar to and possibly identical with the conformation in solution, as shown by measurements sensitive to conformation, for example, the following: the CD spectrum of the dry film is similar to the CD spectrum in solution (Chirgadze & Ovsepyan, 1972); Tempone spin-spin interaction is invariant to hydration (Rupley et al, 1980); enzymatic activity is observed at 0.2 h (Rupley et al, 1980); the thermal stability of lysozyme increases sharply with decrease in hydration below 0.3 h (Fujita & Noda, 1978). Thus, the high hydration conformation of lysozyme is frozen in as the hydration level is reduced.…”
Section: ~0mentioning
confidence: 73%
“…(1) The time-average conformation of lysozyme in the partially hydrated powder is closely similar to and possibly identical with the conformation in solution, as shown by measurements sensitive to conformation, for example, the following: the CD spectrum of the dry film is similar to the CD spectrum in solution (Chirgadze & Ovsepyan, 1972); Tempone spin-spin interaction is invariant to hydration (Rupley et al, 1980); enzymatic activity is observed at 0.2 h (Rupley et al, 1980); the thermal stability of lysozyme increases sharply with decrease in hydration below 0.3 h (Fujita & Noda, 1978). Thus, the high hydration conformation of lysozyme is frozen in as the hydration level is reduced.…”
Section: ~0mentioning
confidence: 73%
“…Zaks and Klibanov studied the cosolvent effect on enzyme catalysis (54, 55) and suggested that some of the hydration water acts as "lubricant" or "plasticizer" that provides the enzyme with sufficient conformational flexibility needed for catalysis. This lubrication is attributed to the ability of water molecules to form hydrogen bonding with the functional groups on the polypeptide chain, and thereby enables the conformational mobility, i.e., the sliding of adjacent polypeptide segments (56). This water species is distinct from that tightly-bound to charged groups which are immobilized by electrostriction (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, until now, precise protein structural transitions promoted by desiccation as well as the reversibility of these processes are not often quantified [34,[40][41][42][43]. The present analysis displays that drying α-chymotrypsin solutions or α-chymotrypsin-montmorillonite suspensions promoted a similar unfolding of at least two different β-structures either in anhydrous and hydrated domains.…”
Section: Discussionmentioning
confidence: 94%